Mortality by Heart Failure and Ischemic Heart Disease in Brazil from 1996 to 2011 - Gaui,Eduardo Nagib (2014)
Background:Circulatory system diseases are the first cause of death in Brazil.Objective:To analyze the evolution of mortality caused by heart failure, by ischemic heart diseases and by ill-defined causes, as well as their possible relations, in Brazil and in the geoeconomic regions of the country (North, Northeast, Center-West, South and Southeast), from 1996 to 2011.Methods:Data were obtained from DATASUS and death declaration records with codes I20 and I24 for acute ischemic diseases, I25 for chronic ischemic diseases, and I50 for heart failure, and codes in chapter XIII for ill-defined causes, according to geoeconomic regions of Brazil, from 1996 to 2011.Results:Mortality rates due to heart failure declined in Brazil and its regions, except for the North and the Northeast. Mortality rates due to acute ischemic heart diseases increased in the North and Northeast regions, especially from 2005 on; they remained stable in the Center-West region; and decreased in the South and in the Southeast. Mortality due to chronic ischemic heart diseases decreased in Brazil and in the Center-West, South and Southeast regions, and had little variation in the North and in the Northeast. The highest mortality rates due to ill-defined causes occurred in the Northeast until 2005.Conclusions:Mortality due to heart failure is decreasing in Brazil and in all of its geoeconomic regions. The temporal evolution of mortality caused by ischemic heart diseases was similar to that of heart failure. The decreasing number of deaths due to ill-defined causes may represent the improvement in the quality of information about mortality in Brazil. The evolution of acute ischemic heart diseases ranged according to regions, being possibly confused with the differential evolution of ill-defined causes.